2019
DOI: 10.1002/slct.201803388
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Highly Conductive Lithium Argyrodites by Means of Lithium Substitution: The Case of Li6Fe0.5PS6

Abstract: All‐solid‐state‐batteries (ASSB) are promising candidates for next generation lithium batteries providing high energy density and safety levels. Their success crucially depends on the properties of the available solid electrolyte materials, ideally offering sufficient conductivities in combination with stability against decomposition over a large electrochemical window. Therefore, the search for solid electrolytes with novel compositions remains of high interest. In this work we present a strategy to stabilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Schneider et al recently reported stabilization of hightemperature Li 7 PS 6 by doping the Li site with iron to form Li 6 Fe 0.5 PS 6 , which exhibits a relatively low ionic conductivity of 1.4 × 10 −4 S•cm −1 . 40 Other groups claimed partial substitution of Al 3+ /B 3+ on the Li site for Li 6 PS 5 X (X = Cl and Br) on the basis of X-ray diffraction (XRD) refinements where Li 5.4 Al 0.2 PS 5 Br exhibits a room-temperature conductivity of 2.4 mS•cm −1 . 41 Another study showed that Y 3+ -doped Li 6 PS 5 Cl exhibits a negligible difference in room-temperature ionic conductivity vis a vis Li 6 PS 5 Cl and that YCl 3 is exsolved in the grain boundary.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Schneider et al recently reported stabilization of hightemperature Li 7 PS 6 by doping the Li site with iron to form Li 6 Fe 0.5 PS 6 , which exhibits a relatively low ionic conductivity of 1.4 × 10 −4 S•cm −1 . 40 Other groups claimed partial substitution of Al 3+ /B 3+ on the Li site for Li 6 PS 5 X (X = Cl and Br) on the basis of X-ray diffraction (XRD) refinements where Li 5.4 Al 0.2 PS 5 Br exhibits a room-temperature conductivity of 2.4 mS•cm −1 . 41 Another study showed that Y 3+ -doped Li 6 PS 5 Cl exhibits a negligible difference in room-temperature ionic conductivity vis a vis Li 6 PS 5 Cl and that YCl 3 is exsolved in the grain boundary.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This could help to create all‐solid‐state batteries not suffering from fast decay due to interfacial decomposition. [ 107 ] While interlayer coatings are more preferable due to better control on morphology and thickness of the layer, the coating layer should be compatible with the cathodic material; a conformal layer needs to be produced between them, facilitating the transfer of Li + ions. On the other hand, the coating layer should be as thin as possible (nanometers) to decrease the migration distance of Li + ions, or the ionic conductivity should be as high as the SSE.…”
Section: Nanoscale Interfacial Engineering At the Cathodementioning
confidence: 99%
“…Interlayer additions, surface coatings, doping, and surface modifications have been studied to find feasible solutions. [19,107] As the biggest problem with Li anodes is the dendritic formation during cycling, hence, this major problem has been studied extensively.…”
Section: Nanoscale Interfacial Engineering At the Anodementioning
confidence: 99%
“…A similar strategy is the substitution of Li + by a metal atom with higher valence, including Mg 2+ , Ca 2+ , Fe 2+ or Al 3+ as shown for Mg 2+ doped Li 4 Ti 5 O 12 , 14 Li 6−x−2y Ca y PS 5−x Cl 1+x , 15 Li 7−2x Fe x PS 6 , 16 or Li 5.4 Al 0.2 PS 5 Br. 17 Besides the increase in mobility it has been observed that phase transitions are influenced as in the case of Li 7−2x Fe x PS 6 16 where by partial substitution of Li + by Fe 2+ the high temperature modification of Li 7 PS 6 was stabilized. 18 The test system in this study is lithium hexasulfidohypodiphosphate Li 4 P 2 S 6 , for which several crystal structures [19][20][21] have been published on the basis of X-ray and neutron diffraction data with the motivation to resolve the unsatisfactory disorder of P sites in the initially published structure.…”
Section: Introductionmentioning
confidence: 99%
“…substitution of M( iv ) and Li + with M( v ) and a vacancy □. A similar strategy is the substitution of Li + by a metal atom with higher valence, including Mg 2+ , Ca 2+ , Fe 2+ or Al 3+ as shown for Mg 2+ doped Li 4 Ti 5 O 12 , 14 Li 6− x −2 y Ca y PS 5− x Cl 1+ x , 15 Li 7−2 x Fe x PS 6 , 16 or Li 5.4 Al 0.2 PS 5 Br. 17 Besides the increase in mobility it has been observed that phase transitions are influenced as in the case of Li 7−2 x Fe x PS 6 16 where by partial substitution of Li + by Fe 2+ the high temperature modification of Li 7 PS 6 was stabilized.…”
Section: Introductionmentioning
confidence: 99%